Innovation, research and development management - Gilbert, Patrick (Great Britain : Wiley, 2018)
The objective of this book is to determine the ways of organizing, managing and leading the research and development (R&D) of a company.
Includes index
Includes bibliographical references p.183-195
mck 17/08/2022
Loans
Keywords: Research, industrial-Management; Technological innovations-Management